#TITLE_ALTERNATIVE# - SITORUS (NIM : 13105052); Pembimbing : Dr. Ir. Zainal Abidin, IRWANDI
IC ADXL335 is a tri-axial accelerometer manufactured by Analog Device, Inc. This IC measures acceleration in the range of Ã‚Â± 3 g. The bandwidth of this IC is in the range of 0.5-1.600 Hz for x and y axes and in the range of 0.5-550 Hz for z axis. This IC has a small dimension with length of 4 mm, width of 4 mm, and thickness of 1.45 mm. To be used for measurement, this IC needs housing. In this research two housings for IC ADXL 335 were designed, modeled, and made. There are two prototypes housing of IC ADXL335 designed, made, and tested in this research. Both of these prototypes were designed using Autodesk Inventor 2010. Prototype 1 has length of 30 mm, width of 30 mm, and height of 35 mm. Meanwhile, Prototype 2 has length of 22 mm, width of 23 mm, and height of 25 mm. Both of these prototypes were modeled using ANSYS 11 to find the natural frequencies and mode shapes. Based on the design and model results, both of these prototypes were then made. Then, the ICs were installed in these housing, each of these prototypes forms a system, i.e. an Accelerometer Prototype 1 and an Accelerometer Prototype 2. Both of these accelerometer prototypes were then tested using a calibration. This testing was done using three pieces of connecting cable, from power supply to the MSA (Multichannel Spectrum Analysis) with length of 2 m, 10 m, and 100 m. Based on the testing results, it can be concluded that both of these accelerometer prototypes have a good performance. They have sensitivity in the range of 270-330 mV/g. In addition, Accelerometer Prototype 1 has a bandwidth of 20-720 Hz and Accelerometer Prototype 2 has a bandwidth of 20-850 Hz.